Criteria for Evaluating the Horizontal Deformation in the Upper Berm and Crest of the Reservoir Dam as a Result of Hydrostatic Pressure and Filtration (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The magnitude of the horizontal pressure generated in the dam body under the influence of the hydrostatic pressure force from the high bef on the reservoir dam depends on the angle of inclination of the soil in the dam body relative to the horizontal plane, its physical and mechanical properties, the frictional forces generated in the areas in contact with the anti-filtration screen and the core, and the structures protecting the dam against horizontal displacement and depends on gravity factors.